2003
DOI: 10.1080/08927014.2003.10382980
|View full text |Cite
|
Sign up to set email alerts
|

Study of erodable paint properties involved in antifouling activity

Abstract: To produce ecological marine paints, it is necessary to understand the phenomena involved in antifouling activity. Due to the multivariable components which have to be taken into account and due to their analytical intricacy, only studies based on selected properties are conceivable. In this study, four properties have been chosen, viz. erosion, biocide release, roughness and the physicochemical characteristics of the film surface. A principal-component analysis (PCA) of the experimental data has shown that, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The paint without additive did not show significant difference of copper release, the copper cumulative release after 28 days was found to be 0.18 µg/cm 2 . These values corroborated with known data of copper release from erodible paints for which the amount of copper release can be relatively weak [19,20]. However, these release rate differences were not significant: whatever the additive, less of 1% of copper thiocyanate was released after 28 days of immersion.…”
Section: Resultssupporting
confidence: 89%
“…The paint without additive did not show significant difference of copper release, the copper cumulative release after 28 days was found to be 0.18 µg/cm 2 . These values corroborated with known data of copper release from erodible paints for which the amount of copper release can be relatively weak [19,20]. However, these release rate differences were not significant: whatever the additive, less of 1% of copper thiocyanate was released after 28 days of immersion.…”
Section: Resultssupporting
confidence: 89%
“…Several attempts have been made to avoid biofilm formation by the incorporation of antimicrobial products into surface materials (Park, Daeschel, & Zhao, 2004;Weng, Chen, & Chen, 1999), by coating surfaces with antimicrobials (Gottenbos, van der Mei, Klatter, Nieuwenhuis, & Busscher, 2001;Thouvenin et al, 2003;Tsibouklis et al, 2000) or by modifying the surfaces physicochemical properties (Rosmaninho et al, 2007;Whitehead, Collingon, & Verran, 2004. Gottenbos et al (2001) demonstrated a reduction in infection rate using silicone rubber implants with covalently coupled quaternary ammonium coatings.…”
Section: Approach For Biofilm Mitigation -Biofilm Preventionmentioning
confidence: 98%
“…However, high velocities have some drawbacks as they produce more compact deposits that are more difficult to remove from the surfaces by both mechanical and chemical methods (Melo and Vieira 1999;Simo˜es et al 2005Simo˜es et al , 2008a. Several attempts have been made to avoid biofilm formation by the incorporation of antimicrobial (AMB) products into surface materials (Weng et al 1999;Park et al 2004) or by coating surfaces with antimicrobials or other materials (Gottenbos et al 2001;Thouvenin et al 2003;Akesso et al 2009;Chen et al 2009). More recently, new low energy surfaces produced by surface bombardment to implant ions such as Mo and F, plasma sputtering and coatings with thin Ni-P-PTFE or DLC (Diamond-LikeCarbon) layers have been developed with an interesting potential for reducing deposit adhesion ).…”
Section: Introductionmentioning
confidence: 99%